2011
DOI: 10.1534/g3.111.000661
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Quantitative Trait Loci Influence the Shape of a Male-Specific Genital Structure inDrosophila melanogaster

Abstract: The observation that male genitalia diverge more rapidly than other morphological traits during evolution is taxonomically widespread and likely due to some form of sexual selection. One way to elucidate the evolutionary forces acting on these traits is to detail the genetic architecture of variation both within and between species, a program of research that is considerably more tractable in a model system. Drosophila melanogaster and its sibling species, D. simulans, D. mauritiana, and D. sechellia, are morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(62 citation statements)
references
References 62 publications
5
56
1
Order By: Relevance
“…In a manner analogous to a study of the posterior lobe of the male genitalia [18,19], a horizontal rspb.royalsocietypublishing.org Proc. R. Soc.…”
Section: (B) Morphological Analysis Of the Ovipositorsmentioning
confidence: 99%
“…In a manner analogous to a study of the posterior lobe of the male genitalia [18,19], a horizontal rspb.royalsocietypublishing.org Proc. R. Soc.…”
Section: (B) Morphological Analysis Of the Ovipositorsmentioning
confidence: 99%
“…melanogaster using a cross between a pair of phenotypically different inbred strains [23]. Here we attempt to replicate these QTL using an independent mapping cross.…”
Section: Introductionmentioning
confidence: 99%
“…If genes that contribute to polymorphism within a species are generally also those that influence a trait difference between species, there should be significant overlap between mapped intra- and interspecific QTL intervals. Several previous studies have observed QTL overlap in both within and between species (Nuzhdin and Reiwitch, 2000; Fishman et al , 2002; Lexer et al , 2005; Hall et al , 2006; Wittkopp et al , 2009; McNeil et al , 2011; Groot et al , 2013), supporting the idea that interspecific differences are not fundamentally distinct from variation within species in many instances. However, at least one study failed to identify any overlap in the positions of QTLs mapped within and between species (Gleason and Ritchie, 2004).…”
Section: Discussionmentioning
confidence: 59%